A ghostly light - Blackwell, Juliet (Blackwell, Juliet. Haunted home renovation mystery., 2017)
When her friend Alicia hires Turner Construction to renovate a historic lighthouse in the San Francisco Bay, Mel Turner can't wait to get her hands dirty. Alicia plans to transform the island property into a welcoming inn, and while Mel has never attempted a project so ambitious--or so tall--before, she's definitely up for the challenge. But trouble soon arises when Alicia's abusive ex-husband shows up to threaten both her and Mel, and later turns up dead at the base of the lighthouse stairs.